Proverbs in Ithaf Zawi Al- istehqaq bi ba'ad Morad Al- Mouradi wa Zawa'ed Abi Ishaq: Grammar study - Alsabih, Sarah Abdullah (Arab Journal for Sciences and Research Publishing, 2020)
Proverbs are a unique example of language creativity among Arabs, and a fertile environment to cite on grammatical rules, especially since Arabs inserted proverbs in their speech when necessary, so it does not change or alter.This research was conducted to study the proverbs included by Ibn Ghazi al- Miknasi in his explanation of Alfiya of Ibn Malik and show the effect of proverbs on his determination of grammar, explaining the extent of grammarians' actual benefit from proverbs in implementing grammar, how they cite proverbs, and how proverbs are mentioned individually at times and sometimes as a supporter of other references. This research studied by surveying and presenting the opinions of the various grammarians. The study concluded that Ibn Ghazi al- Maknisi, like other grammatical rules, was used to construct the bases. And recommending the study of proverbs as linguistic evidence of morphological development.
Keywords: Proverbs; Al-Maknasi; Evidence; The Millennium